2014
DOI: 10.1103/physrevd.90.023519
|View full text |Cite
|
Sign up to set email alerts
|

No quasistable scalaron lump forms afterR2inflation

Abstract: In the Einstein frame picture of Starobinky's R 2 inflation model, cosmic inflation is driven by a slowly rolling inflaton field, called scalaron, and followed by a coherently oscillating scalaron phase. Since the scalaron oscillates excessively many times in its potential, which has a quadratic minimum and is a little shallower than quadratic on the positive side, it may fragment into long-living localized objects, called oscillons or I-balls, due to nonlinear growth of fluctuations before reheating of the un… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 113 publications
(127 reference statements)
0
21
0
Order By: Relevance
“…1 we illustrate the shift in the spectral index due to a nonthermal phase that is implemented after reheating and before BBN. In the left panel we considered the Starobinsky R 2 model that predicts T rh ∼ 10 9 GeV [37], and in the right panel a Starobinsky-like potential with non-gravitational interactions and a linear potential V ∝ φ both characterized by a fiducial reheating temperature T rh = 10 12 GeV. The knowledge of these inflaton features enables the explicit calculation of the n (th) s value, that corresponds to the red dots in the plots.…”
Section: 1mentioning
confidence: 99%
“…1 we illustrate the shift in the spectral index due to a nonthermal phase that is implemented after reheating and before BBN. In the left panel we considered the Starobinsky R 2 model that predicts T rh ∼ 10 9 GeV [37], and in the right panel a Starobinsky-like potential with non-gravitational interactions and a linear potential V ∝ φ both characterized by a fiducial reheating temperature T rh = 10 12 GeV. The knowledge of these inflaton features enables the explicit calculation of the n (th) s value, that corresponds to the red dots in the plots.…”
Section: 1mentioning
confidence: 99%
“…Various aspects of reheating after R 2 inflation have been studied in refs. [16][17][18][19][20][21][22][23]. Ref.…”
Section: Jhep02(2015)105mentioning
confidence: 99%
“…Ref. [23] showed that parametric resonance is not strong enough to form long-living localized objects, and thus reheating proceeds through perturbative decay of the inflaton.…”
Section: Jhep02(2015)105mentioning
confidence: 99%
“…With this observation, Ref. [43] argues that one should count heavy degrees of freedom as well as light degrees of freedom for the β function. This result is taken from Ref.…”
Section: Introductionmentioning
confidence: 99%